Understanding the new international financial reporting standards: the case of IFRS 17 - Jinga, Desire Takudzwa (My University, 2023)
The main objective of this study was to provide an exploratory basis for understanding the application of IFRS 17 by stakeholders in the insurance sector. The objectives of the study were to identify possible, effects of the implementation of IFRS 17 on the eminence of financial reporting in the insurance sector, loopholes that need to be monitored in the implementation of IFRS 17, and adjustments and adaptations to IFRS 17 to perfect financial reporting in the insurance sector. The study adopted an interpretivist philosophy and qualitative approach. An exploratory research design was used. Structured interviews were used to collect data from insurance professionals who were purposively selected for the sample. Thematic content analysis of the responses received revealed that IFRS 17 improves the quality of financial reporting through stable capital requirements for insurers, better transparency and disclosure of insurance liabilities. It also aims to make financial reporting in the insurance sector consistent and more comparable within groups. The study, which is a qualitative study based on a questionnaire, found that the main gaps are in the effectiveness of technological investments in insurers' financial reporting systems, reporting for insurance contracts paid or received before recognition, and inconsistency in the recognition of insurance income and income tax payments. The most significant adjustments relate to the initial calculation of the contractual performance margin, the recognition of insurance proceeds and related income tax charged to the policy holder, and the expansion of the definition of liabilities to cover all obligations. The study concluded that IFRS 17 improves the transparency, uniformity, comparability and consistency of financial reporting by insurance companies. It was recommended that insurance companies implement IFRS 17, conduct staff training to improve staff skills, and advocate for the implementation of adjustments to the new standard. A further
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: IFRS 17; Financial reporting; Insurance sector; SDG-8: Decent work and economic growth